Perancangan Dan Implementasi Company Profile Berbasis Website Sebagai Media Promosi di PT. Hassani Can Packaging - Suwarno Suwarno; Teddy Sanjaya (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
In the current era, the development of information technology is growing rapidly, a lot of information that we can access through the digital world based on the website. One example of the impact of technological developments is that companies are starting to make company profiles. The purpose of this research is to create a company profile for Hassani Can Packaging as a tool and media to be able to reach more and wider areas as well as a means to overcome difficulties in finding new customers. In this study, the waterfall method will be used to design the company profile website, where the website has a homepage, about us, products, career, and contact us.